Environmental Preservation Of Bromo Tengger Semeru National Park Using Green Marketing Strategy - Puspita, Nadya Mega; Julian, Mezi; Ekawaty, Donna; Fahreza, Gilang (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2024)
The establishment of Bromo Tengger Semeru National Park as 10 Priority Tourism Destinations by the Ministry of Tourism, caused Bromo Tengger Semeru National Park to experience a significant increase in visits and also has implications for tourism development in Bromo Tengger Semeru National Park and its surroundings. This shows the weakness of natural tourism management whose success is only measured by the number of visitors. Green Marketing which is carried out sustainably is the result of corrections to the development of mass tourism which has had many negative impacts on the natural environment and local communities. This research aims to identify the impact of tourism on the environment, analyze the market, apply the marketing mix, and develop a Green Marketing strategy for preservation in Bromo Tengger Semeru National Park. Based on the results of the analysis, environmental impacts arise due to a lack of awareness from tourists and the community, a lack of human resources from managers, and mass tourism